Socieconomic Conditions Among the Urban Oldest-Old Females : A Gerontological Study in Medinipur Municipal Town, West Bengal - Chakraborty, Parikshit; Chaudhury, Sutapa; Bandyopadhyay, Arup Ratan (Arthshastra Indian Journal of Economics & Research, 2019)
Gerontology has developed as a discipline to study aged people, and it is becoming a subject of immense significance all over the world. Thus, studies related to this area have a significant role and importance to tackle the problems of the aged people and make a bridge between the socioeconomic needs of the aged and existing resources. However, the term "oldest old" refers to aged individuals who survive in the upper segments of the age pyramid. The present paper aimed to highlight the socioeconomic milieu of the oldest-old women residing in different municipal wards under Midnapore Municipality of Paschim Medinipur district, West Bengal, India. The study explored some basic demographic features as well as other features like housing and living arrangements, different sources of financial support, which dealt with the information related to the economic condition of the oldest old.